INTRODUCING SUSTAINABLE DEVELOPMENT PHILOSOPHY INTO ENGINEERING EDUCATION (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
The paper presents an effort to single out the basic issues of sustainability that could make it applicable for the relevant changes in engineering education .The universities are regarded as change agents and key actors in charge of promoting and achieving sustainable future because of their ability to promote importance of sustainable development (SD) through their scholarly work and public service.